Catching Up: The Role of Demand, Supply and Regulated Price Effects on the Real Exchange Rates of Four Accession Countries - Ronald MacDonald; Cezary Wójcik (Center for Economic Studies and ifo Institute (CESifo), 2003)
The main aim of this paper is to examine the exchange rate behavior of a group of four transitional, EU accession countries, with a view to making policy recommendations regarding their accession to full European Monetary Union. We employ a dynamic OLS panel estimator to investigate the relative importance of demand and supply influences on the exchange rates of these countries. Our analysis shows that both supply- and demand-side effects are important for the accession countries, although their overall effect on inflation differentials and competitiveness seems to be small. An additional focus of the paper is the examination of the role that administrated, or regulated, prices and the productivity of the distribution sector play in the real exchange rate dynamics. Based on a unique database we show that administrated prices have been a powerful force behind price and real exchange developments for our group of accession countries. The distribution sector is shown to have an independent effect on the internal price ratio over-and-above that generated by the BS effect.
Keywords: 330; exchange rates; monetary integration; EMU